2019
DOI: 10.18203/2349-2902.isj20192370
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Tzanakis and Alvarado scoring system in the diagnosis of acute appendicitis

Abstract: Background: Appendicitis is the most common abdominal emergency worldwide. Lifetime risk of acute appendicitis is 8.6% and 6.7% for man and women respectively. Clinical examination is helpful in diagnosis of acute appendicitis in only 70-87% of the cases. To compare Tzanaki and Alvarado scoring system in diagnosing acute appendicitis. Methods: This was a prospective, comparative, cross-sectional study, which was conducted at the Mahatma Gandhi Medical College and Research Institute Hospital. Patients with acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…6,7 In a recent study done in Pakistan, its sensitivity, specificity and overall diagnostic score was determined to be 99%, 91% and 95% respectively 8 indicating that it to be an accurate modality for - ----------------------------------------------------------------------------------------Received on 15-06-2021 Accepted on 25-10-2021 diagnosing of acute appendicitis and preventing a negative laparotomy in this region of the world. 9 However, a prospective study done in 2019 in India concluded that Tzanaki score is considering better diagnostic scoring system than Alvarado score for acute appendicitis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In a recent study done in Pakistan, its sensitivity, specificity and overall diagnostic score was determined to be 99%, 91% and 95% respectively 8 indicating that it to be an accurate modality for - ----------------------------------------------------------------------------------------Received on 15-06-2021 Accepted on 25-10-2021 diagnosing of acute appendicitis and preventing a negative laparotomy in this region of the world. 9 However, a prospective study done in 2019 in India concluded that Tzanaki score is considering better diagnostic scoring system than Alvarado score for acute appendicitis 10 .…”
Section: Introductionmentioning
confidence: 99%